COLLABORATIVE PARTNERSHIPS FOR DIGITAL EDUCATION TO IMPROVE STUDENTS' LEARNING ACHIEVEMENT AT THE INSTITUTE OF ISLAMIC RELIGION OF SULTANMUHAMMAD SYAFIUDDIN SAMBAS, INDONESIA - Ratna Nurdiana; Muhammad Nur Effendi; Kori Puspita Ningsih; Muhammad Ichsan Abda; Aslan (International Journal of Teaching and Learning, 2023)
This study examined the implementation and impact of collaborative partnerships for digital education in improving students' learning achievement at the Institute of Islamic Religion of Sultan Muhammad Syafiuddin Sambas in Indonesia. Digital technologies have become integral to education, offering new opportunities to enhance teaching and learning experiences. The research employed a qualitative approach, utilizing interviews, observations, and document analysis to collect data. Participants, including educators, administrators, technology providers, and students, were selected using purposive sampling. Thematic analysis was conducted to identify key themes related to collaborative partnerships and their influence on learning achievement. The findings revealed that successful partnerships significantly improved students' learning achievement. These partnerships facilitated access to digital resources, provided pedagogical support, and offered technical assistance. Moreover, they fostered a collaborative learning environment, empowering students to engage with digital tools and resources actively. The partnerships also encouraged innovative teaching practices and technology integration into the curriculum. The study's outcomes contribute to the existing literature on collaborative partnerships in digital education and provide insights for educational institutions, policymakers, and practitioners aiming  to  enhance  students'  learning  achievement  through  effective collaborations. The findings highlight the importance of establishing sustainable partnerships and leveraging digital technologies to promote quality education and facilitate student success in the Indonesian context. Further research is recommended to explore additional factors influencing the effectiveness of collaborative partnerships in digital education and their long-term impact on students' learning outcomes.